2020
DOI: 10.1088/1755-1315/430/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Condition of Mangrove Ecosystems in Sungai Apit Siak Distric Based on Standard Damage Criteria and Quality Indicators Mangrove Environment

Abstract: Mangroves are one of the ecosystems in coastal areas that have an important role, but nowadays many are experiencing threats. The purpose of this study was to determine the condition of mangrove ecosystems in Kecamatan Sungai Apit seen from standard criteria for mangrove damage and the indicators of mangrove environmental quality (species association, tree cover, seedling cover and number of seedlings species). This research was conducted in April 2018 in Kecamatan Sungai Apit, Siak Distric. The method used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
1
1
Order By: Relevance
“…Efriyeldi et al 12 found that the population growth of R. apiculata was more clustered and the competition between individuals was very high. The density of mangroves in the mangrove ecosystem of Bukit Batu Village is higher than that obtained by Dewi et al 13 in Kayu Ara Permai Village, Sungai Apit District, Siak Regency, with an average of 2166 ind/ha and Efriyeldi et al 14 in Bunsur Village, Sungai Apit District, namely 1281 ind/ha. This is thought to be due to the better preservation of the ecosystem in this location from disturbance by the community not to cut down indiscriminately.…”
Section: Mangrove Species and Densitycontrasting
confidence: 55%
“…Efriyeldi et al 12 found that the population growth of R. apiculata was more clustered and the competition between individuals was very high. The density of mangroves in the mangrove ecosystem of Bukit Batu Village is higher than that obtained by Dewi et al 13 in Kayu Ara Permai Village, Sungai Apit District, Siak Regency, with an average of 2166 ind/ha and Efriyeldi et al 14 in Bunsur Village, Sungai Apit District, namely 1281 ind/ha. This is thought to be due to the better preservation of the ecosystem in this location from disturbance by the community not to cut down indiscriminately.…”
Section: Mangrove Species and Densitycontrasting
confidence: 55%
“…Apart from that, the diversity in the number of individuals of each type of mangrove based on station is greatly influenced by environmental parameters, this is in line with Ball & Pidsley [12] who stated that the structure of each type of mangrove is very dependent on its ability to adapt to the environment in which it grows and develops. Apart from that, if seen from the temperature side, the Bagik Batu mangrove ecosystem ranges between 29-30 o C, the condition of these environmental parameters is quite good and has an impact on the growth and development of mangroves in Bagik Batu, where, according to Efriyeldi et al [13] the temperature is 30 o C This is the right temperature for mangrove growth.…”
Section: Environmental Parametersmentioning
confidence: 97%
“…Asosiasi spesies ditentukan berdasarkan spesies dominan yang berada dalam suatu komunitas mangrove (Efriyeldi et al 2020). Spesies mangrove yang ditemukan tersebut kemudian diurutkan dari spesies mangrove yang mendominasi hingga spesies mangrove yang tidak mendominasi.…”
Section: Analisis Dataunclassified